(untitled) (Journal of Computational Mathematics, 1985)
In this paper we give a lower bound of the separation sep_F(A,B) of two diagonalizable matrices A and B. The key to finding the lower bound of sep_F(A,B) is to find an upper bound for the condition number of a transformation matrix Q which transforms a diagonalizable matrix A to a diagonal form. The obtained lower bound of sep_F(A,B) involves the eigenvalues of A and B as well as the departures form the normality δ_F(A) and δ_F(B).